65 [videorecording (DVD)] - Beck, Scott, 1984-; Woods, Bryan, 1984-; Driver, Adam; Greenblatt, Ariana, 2007-; Coleman, Chloe; Totino, Salvatore; Bacon, Chris, 1977- (Sony Pictures Home Entertainment, 2023)
"After a catastrophic crash on an unknown planet, pilot Mills quickly discovers he's actually stranded on Earth... 65 million years ago. Now, with only one chance at rescue, Mills and the only other survivor, Koa, must make their way across an unknown terrain riddled with dangerous prehistoric creatures in an epic fight to survive" --Container.